PERBANDINGAN MODEL PEMBELAJARAN INKUIRI DENGAN MODEL PEMBELAJARAN SELF DIRECTED LEARNING TERHADAP KEMANDIRIAN BELAJAR SISWA PADA MATA PELAJARAN TIK (Studi Kasus di SMP Islam Al-Azhar 37 Pekanbaru) - Aulia Devi Syahputri; Melly Novalia; Rahmad Al Rian (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to compare the effect of the Inquiry learning model and the Self-Directed Learning model on students’ learning independence in the ICT subject at SMP Islam Al-Azhar 37 Pekanbaru. The main problem addressed in this research is the low level of students’ learning independence in the ICT subject, which is indicated by a lack of initiative, dependence on the teacher, and low confidence in expressing opinions. This research employed a quantitative approach using a quasi-experimental method. The population of this study consisted of eighth-grade students, with the sample determined through purposive sampling technique. The research instrument was a learning independence questionnaire that had been tested for validity and reliability. Data analysis techniques included normality test, homogeneity test, t-test, and N-Gain test. The results showed that there was a significant difference between the implementation of the Inquiry learning model and the Self-Directed Learning model on students’ learning independence. The average increase in learning independence using the Self-Directed Learning model was 47.61%, while the Inquiry model showed an average increase of 35.11%. Therefore, the Self-Directed Learning model is more effective in improving students’ learning independence in the ICT subject.